FEATURES OF TOTAL, LONGITUDINAL BODY SIZE AND WIDTH OF DISTAL EPIPHYSIS OF LONG BONES OF LIMBS IN HEALTHY AND SICK WITH PYOGENIC SKIN INFECTIONS MEN AND WOMEN - Чаплик-Чижо, І.О. (World of Medicine and Biology, 2015)
Comparison of anthropometric parameters in healthy and patients with pyoderma studied would identify the conditions that cause the peculiarities of dermatoses in patients of different constitutional identity, evaluate functional and adaptive reserves of the body (noninvasive method) and promptly correct found before nosological deviation that becomes the basis of tasks of prevention Medicine - maintaining the health of a healthy person and preventing diseases at risk groups.Aim of our work – define the features of total, longitudinal body size and width of distal epiphysis of long bones of limbs in healthy and patients with pyoderma men and women.Materials and methodsDone clinical laboratory and anthropological examination of 45 patients with pyoderma male and 48 female patients from the Western Ukraine. The results are compared with the data of anthropo-somatotypological examination of 85 healthy men and 135 women of similar age and region of residence from database of Scientific and Research Center Vinnitsa National Medical University named after Pirogov.Used the following methods: general - to verify the diagnosis of pyoderma; anthropometry by the method of V. Bunak in modification of P. Shaparenko; somatotype determination by the method of J. Carter and B. Heath; statistical analysis of the results conducted in statistical package license "STATISTICA 6.0" using parametric and nonparametric methods.Results. DiscussionsIt is established that the value of body length in patients with pyoderma women was significantly greater (p
Keywords: men; women; pyoderma; anthropometry